Iran - "Gupta, Raj Narain" (New Delhi, 1947)
This book covers the following topics Geography and population of Iran; Natural resources of Iran; Agriculture in Iran; Industries in Iran; The oil Industry of Iran;Foreign Trade of Iran; Means of Transport and communications in Iran; Currency and Banking in Iran etc.
Keywords: Iran economic conditions 1945